Diversity and evolution in the barley pathogen Pyrenophora teres - Rau D.; Attene G.; Brown A.H.D.; Nanni L.; Maier F.J.; Balmas V.; Saba E.; Schafer W.; Papa R. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Net blotch is a foliar disease of barley that has a worldwide distribution and can cause substantial yield losses. The casual agent is the heterothallic ascomycetes Pyrenophora teres Drechsler (anamorph: Drechslera teres [Sacc.] Shoemaker). Two morphologically similar intraspecific formae speciales of the net blotch pathogen (that produce different symptoms) are known: the net form (NF) (P. teres f. sp. teres) and the spot form (SF) (P. teres f. sp. maculata). A better understanding of the genetic relationships between these two forms and of the evolutionary potential of the pathogen populations would be useful to improve strategies of resistance breeding and to determine the correct management of the resistance genes for this pathogen. Here, we present and summarize the results of a study aimed at improving our knowledge of the biological and pathological status of P. teres.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)